(untitled) (Research, Society and Development, 2022)
Precast in civil construction provides high technological control and reduction of waste, materials, and time in the construction process. Considering the residues generated in the processes in the production of artifacts, this study aims to investigate the use of precast residues with the addition of rare earth photoluminescent substances in the production of concrete artifacts to illuminate paths. The experiment was carried out in two stages: The first stage was the evaluation of the granulometry after the crushing process, production of traces, and mechanical resistance test. In the second stage, using the best trace, there was the application and test with a photoluminescent substance. The first stage results show the predominance of medium and fine particulates, with a greater amount in sieves with openings of 1.18 mm and 4.75 mm. Regarding the physical properties of concrete, mixture 1 showed a better specific mass, better slump performance, and mechanical strength in cured concrete. Regarding the use of photoluminescent substances in the emission of photons, after exposure to solar radiation, the experiments did not show the desired results.